DAMPAK PENDAPATAN BAGI HASIL AKAD MUZARA’AH, MUKHABARAH TERHADAP KESEJAHTERAAN PETANI DESA BAKEYONG DALAM PERSPEKTIF AL-GHAZALI - Arifatulilmiyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. This research aims to investigate the background of Muzara'ah and Mukhabarah Income Sharing Agreements on the Welfare of Farmers in Bakeyong Village from Al-Ghazali's Perspective. The Bakeyong village community implements cooperation in cultivating land in the form of a muzâra'ah or mukhabarah profit sharing system which can improve the economy of both of them and no one feels at a loss. This research uses a qualitative approach. The data collected was primary data and secondary data using interview data collection with 10 informants. The data analysis used is descriptive data analysis. The results of this research show the importance of empty agricultural land which is not cultivated as the main driver of the practice of profit sharing in Bakeyong Village. This shows the relationship between land availability and the community's decision to implement a profit sharing agreement in the agricultural context. Landowners give their land to other people to manage. The people of Bakeyong village are greatly helped by this profit sharing system and can contribute to increasing economic prosperity. The new finding from this research is that it uses Al-Gazhali's theory, which previously no one had used this theory. Keywords: Muzara’ah, Mukhabarah, Welfare Abstrak. Penelitian ini bertujuan untuk menyelidiki latar belakang Pendapatan Bagi Hasil Akad Muzara’ah dan Mukhabarah Terhadap Kesejahteraan Petani didesa Bakeyong Dalam Perspektif Al-Ghazali. Masyarakat desa Bakeyong menerapkan kerja sama penggarapan lahan dalam bentuk sistem bagi hasil muzâra’ah atau mukhabarah dapat meningkatkan perekonomian keduanya dan tidak ada yang merasa di rugikan. Penelitian ini menggunakan pendekatan kualitatif. Data yang dikumpulkan merupakan data primer dan data sekunder dengan menggunakan pengumpulan data wawancara kepada 10 informan. Analisis data yang digunakan adalah analisis data deskriptif. Hasil penelitian ini, pentingnya faktor lahan pertanian kosong yang tidak digarap sebagai pendorong utama praktik bagi hasil di Desa Bakeyong. Hal ini menunjukkan hubungan antara ketersediaan lahan dan keputusan masyarakat untuk menerapkan akad bagi hasil dalam konteks pertanian. Pemilik tanah memberikan tanahnya kepada orang lain untuk dikelola. Masyarakat desa Bakeyong sangat terbantu dengan adanya sistem bagi hasil ini dan dapat berkontribusi pada peningkatan kesejahteraan ekonomi. Temuan baru dari penelitian ini adalah menggunakan teori Al-Gazhali yang pada sebelumnya belum ada yang menggunakan teori ini. Kata kunci: Muzara'ah, Mukhabarah, Kesejahteraan